The Effect of Digitalization of Payment Transactions on Regional Expenditures in Mamasa Regency - Sabandar, Sita; Sumarni; Baharuddin (Economics and Business Journal (ECBIS), 2025)
This research aims to analyze and determine the effect of digitalization of payment transactions on regional spending in Mamasa Regency. This research is quantitative research using primary and secondary data sources. The primary data source is the results of interviews with Mamasa Regional Government employees who were the research samples where the sample collection method was purposive sampling. Secondary data consists of PAD and regional expenditure data for the last three years as well as other supporting documents. The data collection method is carried out through the following stages: Questionnaire and Interview. The collected data can be analyzed quantitatively using descriptive or inferential statistics to test hypotheses. Analysis of this research data uses regression techniques, namely simple linear analysis. Hypothesis testing is carried out to see the level of significance of the influence of the independent variable on the dependent variable. The research results show that there is a significant positive influence of digitalization of payment transactions on regional spending in Mamasa district.